99m Tc diethylenetriaminepentacetic acid angiotension-coverting enzyme inhibitor renography as screening test for renovascular hypertension in unilateral small kidney: A prospective study - Masood ul Hassan; Shoukat Khan; Mohd Ashraf; Saleem Najar; Feroz Shaheen (World Journal of Nuclear Medicine)
To know the probability of renal artery stenosis (RAS) in unilateral small kidney and function of the unilateral small kidney, which includes glomerular filtration rate, differential function, uptake, Tmax by 99m Tc diethylenetriaminepentacetic acid (DTPA) base and 99m Tc DTPA angiotensin converting enzyme (ACE) inhibition scan. All our patients were subjected to 99m Tc DTPA ACE inhibition renal scintigraphy. All the patients underwent either computed tomography (CT) angiography and magnetic resonance (MR) angiography was done in those patients in which kidney function test was deranged. Renal angiography was subsequently performed in cases with the suggestion of RAS on CT or MR angiography. The quantitative data was expressed as the arithmetic mean, standard deviation and percentages. The intergroup comparisons for parametric data were done by Student′s t-test, whereas non-parametric data was compared with Mann-Whitney U-test. The intergroup comparisons were made by paired t-test and Wilcoxon sign rank test. P <0.05 was considered to be significant, and data was analyzed by Statistical package for social sciences(SPSS-20) software. Out of 47 patients, 25 patients were in the low probability group out of which none was positive for RAS on CT/MR angiography. Out of 47 patients, 12 were in the intermediate group out of which none was positive for RAS. Ten, out of 47 patients were suspected of high probability for RAS by ACE inhibition scan out of which 4 were positive for RAS by CT/MR angiography including one with bilateral RAS. 99m Tc DTPA angiotension-coverting enzyme inhibitor renography is a safe, non-invasive, sensitive, specific, and cost-effective test for excluding renovascular hypertension in patients who have normal or nearly normal renal function in unilateral small kidney.